Role of Audit Committee in Implementing Good Corporate Governance - Endyk M. Asror (Business and Entrepreneurial Review, 2007)
A causal factor of susceptibility of the Indonesia Corporation in facing and econornic turbulence is the weak implementation of Good Corporate Governance (CCG) which comprises of fairness. transparency, accountability and responsibility. Those four principle should be applied simultaneously in order to get an optimum result in measuring a good corporate governance conduct. It seems that there is no strong basis to support the existence of an Audit Committee refers to Corporate Law No. 1/1995. Consequently, the existence of the Audit Committee may cause a legal dispute, for instance it could bring a negative impact when the main objective is to conduct good corporate governance in accordance with basic principles.